PERAN GURU DALAM MEMBANGUN MODERASI BERAGAMA DI SMAN 5 KOTA TASIKMALAYA - Abdul Haris (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2022)
Religious moderation as a point of view can be a solution for mutual openness,accept differences, and maintain inter-religious harmony. Strengthening this moderation should also beintroduced early on to students so that they are not easily influenced by religious thoughts thatextreme, and close themselves to other religions through the role of a teacher of Islam. DestinationThis research is to describe the role of PAI teachers and to find out the supporting andobstacle in building religious moderation in SMA Negeri 5 Tasikmalaya City. This researchusing a descriptive qualitative approach. The place of research is SMAN 5 which has criteriaappropriate in this study. Collecting data using interview and documentation techniques.Data analysis is done by collecting data, reducing data, presenting and interestingconclusion. The validity of the data is done by using sources and triangulation techniques.The results of this study indicate that: 1. The role of PAI teachers in building religious moderation inSMAN 5 Koa Tasikmalaya includes: a. Conservator as PAI teacher is responsible for his attitude,b. PAI teacher transmitters (successors) act as motivators and mentors, c. Innovators(developer) PAI teachers collaborate with all teachers from various religions, d. Teacherorganizers (executors) carry out the innovated activities, e. Transformers, PAI teachertranslating grades by becoming figures for students; 2. The values ​​of religious moderation that are builtamong others; justice (adl), balance (tawazun), simplicity (I'tidal), unity andbrotherhood (ittihad wa ukuwah). 3. Supporting factors and inhibiting factors in buildingModeration of religion in schools include: Supporting factors, namely PAI teachers have self-abilityand very supportive experiences to build religious moderation. Then environmentcommunity that supports school activities, especially religious activities. As for the factorsThe obstacles include the age of the students, which greatly influences the implementation